CLINICAL OUTCOME OF AORTIC SADDLE EMBOLISM – A 10 YEARS’ EXPERIENCE - Muhammad Jamil; Rashid Usman; Amna Shahab (Journal of University Medical & Dental College, 2017)
ABSTRACT: Objectives: To analyse the outcome of aortic saddle embolism (ASE) in patients reporting late to the vascular surgeon. Study design: Descriptive analytical study Place and Duration of study: Department of Vascular Surgery, Combined Military Hospitals Lahore, Gujranwala, Kharian and Quetta from March 2006 to March 2016. Methodology: Data of all the patients with aortic saddle embolism were analyzed for demographic characteristics, co morbidity, surgical intervention performed and outcome in terms of limb salvage and revision procedures. Results: A total of 36 patients were managed during the study period. Thirty (83.3%) patients reported to us six days after the onset of symptoms. Of the total 36, thirty (83.3%) patients had paralysis at the time of presentation. Bilateral femoral embolectomy under local anaesthesia was performed in thirty (83.3%) patients. Three (8.3%) patients underwent open exploration of distal aorta. Amputation rate was 58.3% while 8.3% patients died. Conclusion: Successful management of ASE include high index of suspicion for an early diagnosis, timely referral to and surgical intervention with adequate perioperative anticoagulation.